2013
DOI: 10.1007/s00167-013-2690-x
|View full text |Cite
|
Sign up to set email alerts
|

New method of diagnosis for chronic ankle instability: comparison of manual anterior drawer test, stress radiography and stress ultrasound

Abstract: The results suggest that the value of ATFL length (ATFL stress) and ATFL ratio of stress ultrasound could be used for diagnosis of chronic ankle instability in addition to manual anterior drawer test and stress radiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 31 publications
2
77
0
Order By: Relevance
“…Comparing US results of healthy people and patients with chronic ankle instability, Liu et al reported the differences in the thickness of ATFL [ 51 ] and Croy et al reported differences in the length of ATFL [ 52 ]. Lee et al recommended stress US over regular one for diagnosis of chronic lateral ankle ligament injury [ 53 ]. The study of Cho et al, which was included in the current review [ 38 ], utilized stress US.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing US results of healthy people and patients with chronic ankle instability, Liu et al reported the differences in the thickness of ATFL [ 51 ] and Croy et al reported differences in the length of ATFL [ 52 ]. Lee et al recommended stress US over regular one for diagnosis of chronic lateral ankle ligament injury [ 53 ]. The study of Cho et al, which was included in the current review [ 38 ], utilized stress US.…”
Section: Discussionmentioning
confidence: 99%
“…Hedelin et al revealed that fractures could be examined dynamically to see whether the fractured bone was moving. Lee et al reported that a dynamic scan could be used to diagnose fractures as well as ligament instability. The reason for the increases in fracture detection is because sonography shows widening of the fracture space during the dynamic stress scan.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of chondral fractures in a static condition using sonography and MRI is difficult. However, sonography is a strong tool for use in dynamic conditions and can hence enable the detection of abnormal motion of chondral lesions and mobility of hyperechoic spots along the site of a chondral fracture. Accordingly, the direct diagnosis of chondral fractures is possible by using this modality.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, modern high‐frequency ultrasound transducers used by experienced examiners can provide unsurpassed resolution of the superficial musculoskeletal structures in children . Furthermore, sonography is effective for use in dynamic states, and stress sonography during a manual anterior drawer stress procedure has great specificity in terms of detecting minor instability . When dynamic stress is applied, sonography can easily identify abnormal motion related to chondral fractures.…”
mentioning
confidence: 99%